Phosphorus Dynamics in Sugarcane Fertilized With Filter Cake and Mineral Phosphate Sources - de Aquino Vidal Lacerda Soares, Anelisa; de Mello Prado, Renato [UNESP]; Caione, Gustavo; Rodrigues, Marcos; Pavinato, Paulo Sérgio; Naudi Silva Campos, Cid (Frontiers, 2021)
Organic residual material such as filter cake, combined with mineral phosphate fertilizers, may alter the soil phosphorus (P) bioavailability for sugarcane as a consequence of the competing effect in adsorption sites. This study aimed to quantify the changes in both the inorganic and organic soil P fractions as amended by phosphate fertilizer sources and filter cake and to link the P fractions to sugarcane response. An experiment was conducted in an Oxisol, in a randomized block design with factorial arrangement of 4 × 2, and three replications. Three P fertilizer sources (triple superphosphate, Araxá rock phosphate, and Bayóvar® reactive phosphate) plus a control (no P) were evaluated under both the presence and absence of filter cake. At the end of the second crop cycle, the following were measured: the cane yield, the tissue P content, and soil P fractions. All fertilizer sources were efficient in supplying P to sugarcane. Araxá rock phosphate generated a higher accumulation in moderately labile P, whereas the soluble triple superphosphate resulted in higher labile P. The filter cake, as a source of nutrients and organic matter, has an important contribution to maintain more available P for sugarcane absorption, especially when associated with triple superphosphate. The amount of P absorbed by sugarcane was correlated with the soil labile P (r = 0.58) and also with the inorganic P moderately labile (r = 0.42). Both fractions must be taken into account for a short- to medium-term availability of P for sugarcane in Oxisols.
Keywords: organic matter; oxisol; rock phosphate; soil P lability; triple superphosphate